Blue Madonna - Benn, James R. (Benn, James R. Billy Boyle World War II mystery., 2016)
"Billy Boyle, US Army detective and ex-Boston cop, faces his toughest investigation yet: infiltrating enemy lines in France as the Allies invade Normandy. It's late May 1944. Captain Billy Boyle is court-martialed on spurious charges of black market dealings. Stripped of his officer's rank, reduced to private, and sentenced to three months' hard labor, Boyle is given an opportunity: he can avoid his punishment if he goes behind enemy lines to rescue a high-value Allied soldier. A secret chamber and tunnels, once used by escaping Huguenots in the 17th century, has since been taken over by the Allies. But this "safe house" on the outskirts of Chaumont turns out to be anything but. Two downed airmen, one Canadian and the other American, have been murdered. Billy is flown in as part of a three-man team on June 5, 1944, the night before the Normandy invasion. Billy must solve the mystery of who is behind the murders, then lead a group escape from France back to England, with both the Germans and a killer hot on their heels"--